Analisis Peningkatan Brand Awareness Produk SC Johnson & Son Melalui TikTok - Karunia Suci Kasih Madani; Christian Wiradendi Wolor; Eka Dewi Utari (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This study aims to analyze how TikTok is utilized as a medium to increase brand awareness of PT SC Johnson & Son Indonesia’s products. Amid the dominance of younger generations in the digital landscape, TikTok is considered to have significant potential in reaching consumers through creative and interactive content. Although SC Johnson has actively used this platform, observations and interviews reveal that its content engagement remains relatively low. This research adopts a descriptive qualitative approach with data collected through observation, in-depth interviews, and documentation. The findings indicate that the low effectiveness of the content stems from a lack of relevance to TikTok trends and minimal user interaction. These results lead to recommendations for more adaptive content strategies aligned with young users' preferences, such as storytelling formats, collaborations with influencers, and the use of TikTok features like hashtag challenges and TikTok Live. This study is expected to provide practical contributions for developing TikTok-based digital marketing strategies for FMCG companies in Indonesia.